Sphingolipids as a Culprit of Mitochondrial Dysfunction in Insulin Resistance and Type 2 Diabetes - Roszczyc-Owsiejczuk, Kamila; Zabielski, Piotr (Frontiers in Endocrinology, 2021)
Abstract: Insulin resistance is defined as a complex pathological condition of abnormal cellular and metabolic response to insulin. Obesity and consumption of high-fat diet lead to ectopic accumulation of bioactive lipids in insulin-sensitive tissues. Intracellular lipid accumulation is regarded as one of the major factors in the induction of insulin resistance and type 2 diabetes (T2D). A significant number of studies have described the involvement of ceramides and other sphingolipids in the inhibition of insulin-signaling pathway in both skeletal muscles and the liver. Adverse effects of sphingolipid accumulation have recently been linked to the activation of protein kinase Cζ (PKCζ) and protein phosphatase 2A (PP2A), which, in turn, negatively affect phosphorylation of serine/threonine kinase Akt (also known as protein kinase B (PKB)), leading to decreased glucose uptake in skeletal muscles as well as increased gluconeogenesis and glycogenolysis in the liver. Sphingolipids, in addition to their direct impact on the insulin signaling pathway, may be responsible for other negative aspects of diabetes, namely mitochondrial dysfunction and deficiency. Mitochondrial health, which is characterized by appropriate mitochondrial quantity, oxidative capacity, controlled oxidative stress, undisturbed respiratory chain function, adenosine triphosphate (ATP) production and mitochondrial proliferation through fission and fusion, is impaired in the skeletal muscles and liver of T2D subjects. Recent findings suggest that impaired mitochondrial function may play a key role in the development of insulin resistance. Mitochondria stay in contact with the endoplasmic reticulum (ER), Golgi membranes and mitochondria-associated membranes (MAM) that are the main places of sphingolipid synthesis. Moreover, mitochondria are capable of synthesizing ceramide though ceramide synthase (CerS) activity. Recently, ceramides have been demonstrated to negatively affect mitochondrial respiratory chain function and fission/fusion activity, which is also a hallmark of T2D. Despite a significant correlation between sphingolipids, mitochondrial dysfunction, insulin resistance and T2D, this subject has not received much attention compared to the direct effect of sphingolipids on the insulin signaling pathway. In this review, we focus on the current state of scientific knowledge regarding the involvement of sphingolipids in the induction of insulin resistance by inhibiting mitochondrial function.